2017
DOI: 10.1177/0022167817702783
|View full text |Cite
|
Sign up to set email alerts
|

Existential Anxiety, Personality Type, and Therapy Preference in Young Adults

Abstract: The current study examines the relationship between existential anxiety (EA), personality traits, and therapy preference in a sample of young adults. EA is thought to be universal human experience, yet no published research has been conducted on whether certain personality traits predict higher levels of EA. Males and females ( N = 69) aged 18 to 25 years completed several self-report measures, including a measure of EA, five-factor personality traits, and therapy preference (insight- vs. action-oriented). Pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…However, the findings on the links between shyness and some existential concerns are congruent with existing data showing high neuroticism (e.g., shyness and shame) among youth with elevated existential anxiety (Shumaker et al, 2020) as well as high (social) anxiety and emotional dysregulation levels among shy individuals (Bowker et al, 2017; Mounts et al, 2006; Nelson, 2013; Nelson et al, 2008). On the one hand, high levels of search for meaning among shy young people may indicate that they are motivated for meaning making (Heintzelman & King, 2014).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, the findings on the links between shyness and some existential concerns are congruent with existing data showing high neuroticism (e.g., shyness and shame) among youth with elevated existential anxiety (Shumaker et al, 2020) as well as high (social) anxiety and emotional dysregulation levels among shy individuals (Bowker et al, 2017; Mounts et al, 2006; Nelson, 2013; Nelson et al, 2008). On the one hand, high levels of search for meaning among shy young people may indicate that they are motivated for meaning making (Heintzelman & King, 2014).…”
Section: Discussionsupporting
confidence: 85%
“…Within Tillich's (1952) framework, existential anxiety, or ultimate apprehension about the meaning of life and death, comprises three dimensions: (a) fate and death, that is, the relative apprehension about the contingency of life, our role in it, and the absolute threat of death to one's being; (b) emptiness and meaninglessness, that is, the relative fear that specific beliefs no longer have the meaning they once had and the absolute concern about the loss of the significance of life, the world, and the future; and (c) guilt and condemnation, that is, the relative anxiety that one's behavior has not lived up to one's standards and the absolute concern that one's life has not met certain universal standards concerning moral and ethical identity. Adults (including emerging adults) with high existential anxiety have been found to experience more depression, anxiety, identity distress (Weems et al, 2004), and neuroticism such as proneness to shyness, shame, embarrassment, and guilt (Shumaker et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…After arriving at the lab, participants were asked to complete the NEO Five-Factor Inventory [24], which is one of the most widely used measures of the Five-Factor Model with 60 items and has been affirmed in a number of studies [25][26][27]. This inventory can measure five factors of an individual's personality, including neuroticism, agreeableness and conscientiousness, extraversion and openness.…”
Section: Scale Measurementmentioning
confidence: 99%
“…4 EA is known to be a universal human experience and people experience the same at various turning points in life. 3,5 A study found that EA concerns are common among adolescents, and are associated with psychological symptoms, as well as identity issues. 6 Scarce, yet pertinent research has revealed that some young adults may be experiencing seemingly intense EA.…”
Section: Introductionmentioning
confidence: 99%
“…6 Scarce, yet pertinent research has revealed that some young adults may be experiencing seemingly intense EA. 5 In the current times, social media is flooded with posts having an existential theme, be it existential dread or existential humour. 7 Though, research has indicated that humour acts as a buffer of EA, 8 it remains to be seen if EA is just for the humour or a result of the feeling of existential angst and their active coping with it.…”
Section: Introductionmentioning
confidence: 99%